Instructional Strategies that Respond to Global Learners’ Needs in Massive Open Online Courses - Trang Phan (Online Learning, 2018)
Massive Open Online Courses (MOOCs) are one of the most innovative forms of online instruction delivered to learners of different language, cultural and educational backgrounds around the world. These multicultural learners have diverse communication styles, learning behaviors and needs that are manifested and demonstrated differently in such a large scale online learning environment as MOOCs. There is little research on how aspects of MOOC learners’ diverse cultural backgrounds and learning behaviors are perceived, how these learners are characterized in terms of their learning needs, and how the MOOC instructors and instructional designers respond to these needs in the course design process.